The assessment of health status among patients with COPD - Curtis, J.R; Patrick, D.L (The European respiratory journal, 2003)
Survival and physiological measures alone do not represent the full experiences of patients with chronic obstructive pulmonary disease. Reducing the personal and social burden of disease by improving patients' symptoms, functional status and quality of life are also important goals. There has been a substantial increase in the use of newly developed tools that measure health status and it is important for clinicians and researchers to understand these instruments' strengths and weaknesses in providing insight into a patient's condition and experience. Relying only on mortality and physiological outcomes could blind a clinician to significant benefits patients may receive from a treatment. A growing body of research utilises end-points assessed directly by patients whose self-reported health status includes health-related quality of life and functional status. This article reviews major concepts and methods in health-status assessments for patients with chronic obstructive pulmonary disease, which will have an important role in assessing the efficacy and effectiveness of new treatments.